EFEK EKSTRAK ETANOLIK DAUN JAMBLANG (Syzygium cumini (L) skeels) TERHADAP FAKTOR VIRULENSI Streptococcus mutans ISOLAT DARI KARIES GIGI ANAK USIA PRASEKOLAH - , Suzanna Sungkar ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Caries is a major dental problem in children. The main bacterial cause of dental caries is Streptococcus mutans. This bacterium has virulence properties involved in the formation of biofilm on the tooth surface. Oral condition of children is often exposed to food and beverages containing sucrose, can affect the virulence of S. mutans. Jamblang (Syzygium cumini) leaves are potentially as anticariogenic material due to its antibacterial effect. The purpose of this study was to investigate antibacterial potency and effect of ethanolic extract of Jamblang leaves against virulence factors of S. mutans isolates from childrenâs caries, that is water-insoluble glucan synthetizing, acid production, and adhesion of S. mutans to hydroxyapatite. Analysis of the active compounds of the extract was carried out using thin layer chromatography (TLC) and Liquid Chromatograph-Mass Spectrography (LC-MS). Samples of S. mutans were isolated from childrenâs carious deciduous molar teeth. The experiment of virulence factors of S. mutans was carried out by analysing the effect of the extract concentration on the water-insoluble glucan synthetizing, acid production, and adhesion of S. mutans to hydroxyapatite. The concentrations of extract tested were 22.5%, 20%, 15%, and distilled water as a negative control. Non-parametric Kruskal-Wallis test was used to analyse data of this study. The results of TLC and LC - MS analysis showed the presence of flavonoid, tanin, and terpenoid in the leaves. Effect of extractâs concentration on the growth, water insoluble glucan synthesizing, and adhesion of S. mutans to hydroxyapatite were significant different (p<0.05) among groups. The concentration of ethanolic extract of 22.5% gave the greatest effect on the growth, on water-insoluble glucan synthetizing and on adhesion of S. mutans compare to the other two concentrations . The effect of ethanolic extract of Jamblang leaves against pH culture of S. mutans based on time contact increased significantly (p<0.05) between momentary contact to a contact time of 1 hour, and between contact time of 1 hour to 8 hour. The effect of ethanolic extract of Jamblang leaves against pH culture of S. mutans based on the concentrations of the extract were significantly different (p<0.05) between the concentrations of 15% with 20 %, and that of 15% with 22.5 %. It can be concluded that the ethanolic extract of Jamblang leaves has antibacterial potency against S. mutans isolated from deciduous dental caries of child. Minimal inhibitory concentration is 200 mg/ml, and minimum bactericidal concentration is 225 mg/ml. Effect of extractâs concentration of 22.5% in reducing the number of S. mutans, inhibitoring water-insoluble glucan synthetized, and adhesion to hydroxyapatite is better than the other two concentrations. There is no difference in the reduction of acid production between the ethanolic extract concentration of 22.5%, 20% and 15%.